Tambo Inga: Perceptions and heritage valuation of the walls of my community - Gómez Calderón, Tania Elisabeth (2022)
The Tambo Inga Archaeological Site, during a long process has endured the changes demanded by the urban development of the district of Puente Piedra, these changes have generated a reduction of the archaeological area due to the demand of new uses and spaces, so the main objective of this research is to determine which are the most predominant patrimonial values about Tambo Inga perceived by the patrimonial subjects and to understand what is the vision for this archaeological site in conjunction with its surroundings. The method used is to conduct surveys and interviews with heritage subjects, which include the views of public administration institutions, professionals related to the research topic, and society, including local residents who have daily contact with the site and cultural groups that work to disseminate information about the monument, as well as visits to the area. The aim is to know the current state, obtaining as results the cultural appropriation of Tambo Inga and the perspective of achieving the value enhancement to turn the huaca into a cultural tourist attraction in northern Lima.